Mencetak Wirausaha Muda Universitas Ma Chung - Sunday Noya; Etsa Astridya Setiyati; Dian Wijayanti (Jurnal ABM Mengabdi, 2016)
Wirausaha Muda Bernas is the Entrepreneurs Development Program at Universitas Ma Chung which is supported by a entrepreneurship grant from The Indonesian Ministry of Research, Technology, and Higfer Education. The program is implementing the overall formation of entrepreneurial activities ranging from the formation of mindset, development of business ideas, until the incubation program therein do mentoring, training and coaching that covering all aspects of business. Aspects that include product development, feasibility study, market research, strategy and production technology, management and business development, marketing and promotion strategy as well as supporting other aspects such as business licenses, financial management, tax, legal and law, intellectual property rights, environmental aspect, and halal certification. Tenant will then be facilitated and pushed to have a sustain business.All the activities of training and coaching are done a team consisting of lecturers and practitioners who are competent in the field of entrepreneurship. To cover all aspects of entrepreneurship, the team will be assisted by several other facilitators consisting of lecturer, practitioners who are competent in their respective field and entrepreneurs who have been successful with their business. Hopefully this program will not only give birth to young entrepreneurs fostered independently of tenants, but also the formation of an independent institution and sustainable entrepreneurship unit that serves to build entrepreneurship among students at the Universitas Ma Chung as well as many comprehensive young entrepreneurs. Hopefully this small action can contribute to the development of entrepreneurship in Indonesia.